2068. Molecular and Clinical Features of New HIV-1 diagnoses in Northern Dominican Republic. (15th December 2022) - Sanchez, Martha C; Lerebours, Alain; Darpolor, Josephine; Manne, Akarsh; Novitsky, Vladimir; DeLong, Allison; McCarthy, Meghan; Carlo, Dominique; Solomon, Matthew; Rodriguez, Claudia; Kantor, Rami
Abstract: Background: Surveillance of transmitted drug resistance (TDR) and molecular epidemiology of newly diagnosed persons with HIV can impact care and prevention and inform efforts towards ending the HIV epidemic. Both interventions are not routinely available in the Dominican Republic (DO). Methods: During 10/2019-4/2021, we attempted to enroll all newly HIV-diagnosed antiretroviral naïve adults (≥18 years) presenting at the regional hospital in Santiago, DO. Demographic, clinical and laboratory data were collected, and blood samples obtained for partial pol genotyping. Subtyping and resistance interpretation were done with Stanford Database tools. Maximum likelihood phylogenies were inferred by RAxML and clusters were defined as clades with bootstrap support of ≥0.8. Extended phylogenetic analyses included ∼1, 500 publicly available Caribbean sequences. Demographics and TDR were compared by cluster status using Fisher Exact or Wilcoxon rank sum tests. Results: Of 100 HIV-diagnosed participants (mean age 40 years; 61% male; 84% heterosexual; 50% never tested prior), 56% were hospitalized, 48% tested via doctor advise and 28% for feeling sick. Available CD4 count was < 200 cells/µL in 49% (43/87) more prevalent (vs CD4 >200) in heterosexuals (93% vs 7% in gay/bisexuals; p=0.003). Genotyping from 68/100, were 29% HIV-1 subtype B, 69% B-containing recombinants and one HIV-1 subtype C. TDR was in 12% (95% CI: 5-22%), all to NNRTIs (K103N and Y188L most common; two with multiple mutations). Six identified clusters included 25% of participants, 92% from downtown Santiago. Individuals in the largest 6-member cluster met partners online and were gay/bisexual. Participants in clusters had higher TDR (24% vs 8%, p=0.100), were younger (34 vs 43 years, p=0.01), and were gay/bisexual (41% vs 8%, p=0.003). In extended phylogenetic analyses participant sequences clustered with other DO sequences, as well as some from Haiti. Conclusion: In this snapshot of new HIV diagnoses in the DO, findings of high AIDS at diagnosis, particularly in heterosexuals, high TDR, more clustering in gay/bisexual younger individuals, and existing non-local-only transmission networks, should inform focused surveillance and prevention strategies to disrupt HIV transmission and improve care. Disclosures: All Authors : No reported disclosures.